"Instead of Asking for Fare, You Ask Her to Pay with Sex": Male Perspectives on the Factors Influencing Schoolgirls' Participation in Age-Disparate Transactional Sex Relationships - Leso Munala; Asha Mohamed; Nene Okunna; Bethlehem Yewhalawork; Paul Kibati; Jesse Kihuha (MDPI AG, 2023)
Age-disparate transactional sex relationships are often coerced and exploitative. The gender and economic disparities between affluent men and economically disadvantaged girls often perpetuate these relationships, resulting in their exploitation. This qualitative study assessed men's understanding of factors influencing schoolgirls' engagement in age-disparate transactional sex relationships in two rural districts in Kenya. Four focus group sessions were conducted with men from two primary professions: motorcycle taxi operators (Boda Boda) and teachers from primary and secondary schools from two districts in Kitui South, Sub County, Kenya. Focus group data were analyzed using conventional content analysis. Several influential factors associated with schoolgirls' engagement in these transactional relationships are discussed in three broad themes: access and coercion, parental influence, and peer-related factors. Study results indicate that schoolgirls in rural areas are more susceptible to predation by men willing to trade sexual favors with underage girls. These findings make it imperative to address the predation of adolescent girls by men involved in these transactional relationships by implementing comprehensive sex education programs that empower schoolgirls to recognize and resist coercion. Additionally, implementing measures involving community leaders, parents, and other stakeholders in a collective effort to combat the exploitation of underage girls is paramount. These measures should be accompanied by the stricter enforcement of laws and regulations to hold perpetrators accountable for their actions.